Automation of Welding Fumes based on MQ-2 Sensor in Welding Laboratory. - Bambang Adi Wahyudi; Duwi Leksono Edy; Wiyono wiyono (Labor Dasar dan Sentral Universitas Andalas, 2020)
In practical welding activities, there are potential hazards that must be addressed. These potential hazards include exposure to toxic fumes and dust. Fumes in the welding process contain a lot of metal oxides and can cause chronic effects in the form of eye irritation, sensory irritation, and impaired lung physiological function. Therefore, an air intake sistem is needed to minimize the volume of fumes in the welding chamber . This study aims to design an automation of exhaust smoke using the sensor module, microcontroller and actuator. The resulting tool is equipped with a display of detected air quality conditions, and an alarm indicating that the air quality is in a dangerous level. The method used is experimental development with 3 main stages, namely: designing hardware and software, testing the tools and analyzing their work functions. The results obtained are that the MQ-2 sensor is able to detect changes in the concentration of welding smoke and can be used as an analog input to control the work of the indicator lights, alarms and exhaust fans. The average ability of the exhaust fan to absorb the smoke concentration in the welding chamber is 26.85 seconds for 33 ppm at 40 mm long welding and 29.51 seconds for 37 ppm at 80 mm long welding process. With this capability, this tool can be used as a technical solution related to Occupational Health and Safety in welding laboratories.